1991
DOI: 10.1111/j.1476-5381.1991.tb12413.x
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural properties of CI‐988, a selective cholecystokininB receptor antagonist

Abstract: 1 The behavioural effects of a selective cholecystokininB (CCKB) receptor antagonist CI-988 were investigated in rodents. 2 In three rodent tests of anxiety (rat elevated X-maze, rat social interaction test and mouse light/dark box) CI-988 over the dose range 0.001-I0.Omgkg 1, (i.p.) produced an anxiolytic-like action. The magnitude of this effect was similar to that of chlordiazepoxide (CDP). In contrast, the selective CCKA receptor antagonist, devazepide, was inactive. CI-988 also showed anxiolytic-like act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(46 citation statements)
references
References 38 publications
3
43
0
Order By: Relevance
“…Conversely, systemic administration of the CCK B receptor antagonist L-365,260 attenuates fear-potentiated startle in rats (Josselyn et al, 1995a). These results are consistent with the anxiogenic and anxiolytic effects of systemically administered CCK B agonists and antagonists, respectively, in a range of behavioral paradigms including the elevated plus maze, light-dark box, punished responding, and social interaction (see, for example, Hughes et al, 1990;Harro and Vasar, 1991;Rataud et al, 1991;Singh et al, 1991;Männistö et al, 1994;Rex et al, 1994). These studies suggest that CCK B receptors mediate a constellation of behaviors associated with "anxiety" (see, for example, Harro et al, 1993).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Conversely, systemic administration of the CCK B receptor antagonist L-365,260 attenuates fear-potentiated startle in rats (Josselyn et al, 1995a). These results are consistent with the anxiogenic and anxiolytic effects of systemically administered CCK B agonists and antagonists, respectively, in a range of behavioral paradigms including the elevated plus maze, light-dark box, punished responding, and social interaction (see, for example, Hughes et al, 1990;Harro and Vasar, 1991;Rataud et al, 1991;Singh et al, 1991;Männistö et al, 1994;Rex et al, 1994). These studies suggest that CCK B receptors mediate a constellation of behaviors associated with "anxiety" (see, for example, Harro et al, 1993).…”
supporting
confidence: 69%
“…Because systemically and i.c.v. administered CCK B agonists produce a broad range of autonomic and behavioral changes associated with "anxiety" (Singh et al, 1991;Harro et al, 1993;Belcheva et al, 1994), it is possible that the activation of amygdala CCK B receptors may result in the expression of a large number of behavioral and autonomic changes associated with "anxiety" or "fear." Consistent with this proposal is the finding that endogenous CCK-4 levels are elevated in the amygdala in rats after exposure to a predatorscented cloth (Pavlasevic et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These results appear striking since CCK2 receptors activation (especially the CCK2a subtype) by CCK agonists has been shown to be involved in stress-related behaviors leading to anxiogenic-like responses in mice (Harro et al 1993;. In addition, most of the studies have shown that the blockade of CCK2 receptors by selective antagonists induces anxiolytic-like responses in rodents (Rataud et al 1991;Singh et al 1991;Derrien et al 1994; see also reviews in Harro et al 1993;Shlik et al 1997;Daugé and Léna 1998). Therefore, the lack of behavioral modifications observed with CCK2 receptor-deficient mice, could be related to unknown compensatory processes.…”
Section: Discussionmentioning
confidence: 91%
“…Iontophoretic application of the watersoluble benzodiazepine, flurazepam, produced a selective block of CCK-induced increases in firing rate of CAl and CA3 hippocampal neurones in vivo (Bradwejn & De Montigny, 1984), an effect that was reversed by application of flumazenil. They proposed that this selective block of CCK responses by benzodiazepines acting via neuronal benzodiazepine receptors could account for the anxiolytic effects of these drugs, which is made more interesting by recent evidence that CCK11 antagonists are also potent anxiolytics (Hughes et al, 1990;Singh et al, 1991). Benzodiazepine inverse agonists have been shown to induce panic (Dorrow et al, 1983;Baldwin & File, 1988;Little, 1991).…”
Section: Introductionmentioning
confidence: 99%